2015
DOI: 10.3897/zookeys.508.8926
|View full text |Cite
|
Sign up to set email alerts
|

Malalcahuello ocaresi gen. & sp. n. (Elateridae, Campyloxeninae)

Abstract: Malalcahuello ocaresi gen. n. & sp. n., from Chile, is described and compared with Campyloxenus pyrothorax Fairmaire & Germain, 1860.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…They differ from Sinopyrophorinae in having the flabellate antennae, deep antennal cavities lying beneath the hypomera, and membranous tarsal lobes (Costa 1984a, Costa et al 2010). The members of the subfamily Campyloxeninae, which have not been included in any DNA-based study to date, differ from Sinopyrophorinae by much wider frontoclypeal region with a complete frontal carina (frontoclypeal region strongly protruding, relatively narrow and high, longitudinally carinate medially in S.schimmeli ), narrowed apical portions of lateral lobes of mesoventrite (wide in S.schimmeli ) oval-shaped mesoventral cavity (elongate, gradually narrowed posteriorly in S.schimmeli ), abdomen with five ventrites and without a luminous organ (six or seven ventrites, and a large abdominal luminous organ in S.schimmeli ), distinctly longer paraprocts, differently shaped aedeagus with the median lobe longer than parameres, and the paramere elongate, with a subapical hook, and apex oriented posteriorly (Costa 1975, Arias-Bohart 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They differ from Sinopyrophorinae in having the flabellate antennae, deep antennal cavities lying beneath the hypomera, and membranous tarsal lobes (Costa 1984a, Costa et al 2010). The members of the subfamily Campyloxeninae, which have not been included in any DNA-based study to date, differ from Sinopyrophorinae by much wider frontoclypeal region with a complete frontal carina (frontoclypeal region strongly protruding, relatively narrow and high, longitudinally carinate medially in S.schimmeli ), narrowed apical portions of lateral lobes of mesoventrite (wide in S.schimmeli ) oval-shaped mesoventral cavity (elongate, gradually narrowed posteriorly in S.schimmeli ), abdomen with five ventrites and without a luminous organ (six or seven ventrites, and a large abdominal luminous organ in S.schimmeli ), distinctly longer paraprocts, differently shaped aedeagus with the median lobe longer than parameres, and the paramere elongate, with a subapical hook, and apex oriented posteriorly (Costa 1975, Arias-Bohart 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Campyloxeninae were placed into Pyrophorini by Stibick (1979) but this was not accepted by later authors (see e.g., Costa et al 2010). In fact, the members of Campyloxeninae differ diagnostically from Pyrophorini in e.g., the absent setae on tarsal claws, presence of the wedge cell in the hind wing venation and the ovispositor with styli (Costa 1975, Arias-Bohart 2015). Current molecular phylogeny suggests at least three independent origins of bioluminescence within Elateridae, i.e., in Agrypninae: Pyrophorini, Sinopyrophorinae and Thylacosterninae.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the tropical American Pyrophorus noctilucus is considered the largest (~30 mm) and brightest bioluminescent insect ( Harvey and Stevens, 1928 ; Levy, 1998 ). All luminous species are closely related - luminous click beetles belong to the tribes Pyrophorini and Euplinthini ( Costa, 1975 ; Arias-Bohart, 2015 ) of the subfamily Agrypninae, with the single exception of Campyloxenus pyrothorax (Chile) in the related subfamily Campyloxeninae ( Stibick, 1979 ). The luminescence of a pair of pronotal ‘light organs’ of the adult Balgus schnusei ( Costa, 1984 ), a species that has now been assigned to the Thylacosterninae of the Elateridae ( Costa et al, 2010 ), has not been confirmed by later observation.…”
Section: Photinus Pyralis Additional Informationmentioning
confidence: 99%
“…For instance, the tropical American Pyrophorus noctilucus is considered the largest (~30 mm) and brightest insect (139,140). All luminous species are closely related -luminous click beetles belong to the tribes Pyrophorini and Euplinthini (138,141) of the subfamily Agrypninae, with the single exception of Campyloxenus pyrothorax (Chili) in the related subfamily Campyloxeninae (142). The luminescence of a pair of pronotal 'light organs' of the adult Balgus schnusei (143), a species that has now been assigned to the Thylacosterninae of the Elateridae (137), has not been confirmed by later observation.…”
Section: Taxonomy Biology and Life Historymentioning
confidence: 99%